2021
DOI: 10.3390/ijerph182111558
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Long-Term Survivorship Care for Cancer Patients in OECD Countries: A Systematic Review for Decision-Makers

Abstract: Long-term cancer survivorship care is a crucial component of an efficient healthcare system. For numerous reasons, there has been an increase in the number of cancer survivors; therefore, healthcare decision-makers are tasked with balancing a finite budget with a strong demand for services. Decision-makers require clear and pragmatic interpretation of results to inform resource allocation decisions. For these reasons, the impact and importance of economic evidence are increasing. The aim of the current study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…The formers were assigned only once to the corresponding cycle of occurrence; the latter were assigned to the patient annually, from the date of complication/comorbidity until death, except for de novo malignancies and HBIG prophylaxis. Consistent with other modeling approaches ( 30 ), the annual costs of de novo malignancies started in the incident year throughout the five subsequent years.…”
Section: Methodssupporting
confidence: 78%
“…The formers were assigned only once to the corresponding cycle of occurrence; the latter were assigned to the patient annually, from the date of complication/comorbidity until death, except for de novo malignancies and HBIG prophylaxis. Consistent with other modeling approaches ( 30 ), the annual costs of de novo malignancies started in the incident year throughout the five subsequent years.…”
Section: Methodssupporting
confidence: 78%
“…The early implementation of palliative care is requested by the reduced cognitive ability of brain tumor patients [ 9 ] and by the heavy distress that is experienced by caregivers. Moreover, in the context of the heavy socioeconomic burden of cancer [ 10 , 11 ], it has been shown that early palliative care activation reduces the costs of hospitalizations [ 12 ] and leads to an increase in home discharge for end-of-life care [ 13 ]. In most of the cases discussed here, caregivers had to face a sudden worsening of patients’ neurological conditions without having the possibility to set up adequate domestic assistance: this can explain the low rate of home deaths in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-makers require clear interpretation of EEs results to inform reimbursement decisions [ 5 ]. Notably, the adequacy of reporting various elements of any health economic evaluation is imperative to benefit the understanding and interpretation of these studies.…”
Section: Introductionmentioning
confidence: 99%